Pengaruh Model Pembelajaran Project Based Learning terhadap Keterampilan Menulis Teks Berita Siswa Kelas VII SMP Negeri 2 Pariaman - Agung Maulana Irsyad; Dewi Anggraini (Lembaga Pengembangan Kinerja Dosen, 2023)
In Merdeka Curriculum on junior high school education for class VII, one of the writing skills that students must master is news writing. The study is set back by a researcher's curiosity about the influence the model of learning project based learning on the ability to write a low student news text. The purpose of this study is to know how the application of project based learning models has affected students' ability to write news texts. This type of research is quantitative with experimental methods. The population in this study is the entire class vii for the state junior year 2022/2023 which numbered 212 students represented by the sample as many as 32 students selected using purposive sampling. Data on this research is the score of text messages test before and after using the learning model project based learning. The study has shown that the use of project based learning models is supported by an increased average of students' grades from a staggering 75 with more than enough qualifications (Ldc) to an 85.02 with good qualifications (B).